Effective M3Y-P2 interaction of study nuclear energy levels for 48Ti in fp shell model - Najm, Kareem S.; Majeed, Firas Z. (Edelweiss Applied Science and Technology, 2024)
In the fp-shell area of the 48Ti isotope (Z=22, N=26), examine the nuclear excitation energies using the nuclear shell model. The energy levels, total angular momentum, and parity of the nucleons outside the locked core 40Ca are calculated using the OXBASH algorithm for GX2, GX1A, KB3, and effective M3Y-P2 interactions. mixing together two orbital configurations. There was a good agreement between the model space vectors and energy levels and experimental data, but the agreement decreased when the realistic M3YP-2 interaction was used. The core polarisability effect has been used to accommodate the rejected space: core and higher organization via the L-S shell with an effective M3Y-P2 interaction. A comparison of the theoretical and experimental results has been conducted.